Unexpected outcome of a modification of Bracka repair for proximal hypospadias: High incidence of diverticula with flaps - (:unkn) unknown (ELSEVIER SCI LTD, 2016)
Introduction Various graft and flap techniques have been proposed for urethral reconstruction in proximal hypospadias repair. The Bracka repair involving the transfer of inner prepuce like aWolfe graftmostly results in satisfactory results besides a high fistula rate. Aim The aim was to decrease the high fistula rate with Bracka repair; we wanted to use the advantages of vascularized skin in the Brackamethod. The aim of this studywas to evaluate our results with this modification. Study design Our modification involves using a flap instead of a graft. In the first stage, chordee was corrected by transection of the urethral plate and dorsal midline plication when necessary. Instead of a graft as suggested by Bracka, inner preputial skin with ample blood supply was transferred and stitched to the denuded ventral penile surface. In the second stage after 6 months, this flap was tubularized in the ThierscheDuplay fashion. Hospital records of patients who had undergone two stage modified Bracka repair between June 2007 and July 2012 were reviewed, including complaints, complications, and need for interventions. Results Thirty-eight patients had undergone this operation. Four patients were lost to follow-up. The main complaint was obstructed urinary flow. Voiding symptoms were first attributed to urethral stenosis, but were, however, found to be due to diverticulum and vortex of the urine in the dilated urethra. Twenty-one patients (61%) had voiding problems and 10 patients (29%) had urinary tract infections. Fistula was observed in 23 and diverticula were observed in 24 patients. Of these, 16 patients had both fistula and diverticula. Only two patients (5%) were free of complications and totally satisfied with the operation, and 23 of the 34 patients had complications requiring intervention (Figure). Discussion Inner preputial flaps used in proximal hypospadias repairs are prone to diverticula formation. They become redundant in time requiring reoperation, thus decreasing the success rate. Careful fixation of the flap to the corpora and allowing time for additional attachment of the urethral plate substitution through fibrotic activity could not overcome this complication. Conclusion Our modification of the Bracka technique using a flap for the plate resulted in a high rate of complications (in particular diverticulum formation) and was therefore abandoned. We recommend careful use of flaps in hypospadias surgery and long-term follow-up studies to evaluate actual functional and cosmetic results.
Keywords: Proximal hypospadias; Bracka repair; Flap; Graft; Diverticulum; Two-stage repair